Analisis Faktor-Faktor Yang Mempengaruhi Indeks Pembangunan Manusia Di Provinsi Nusa Tenggara Timur - Fransiskus Apriliano Lay (Ekopem: Jurnal Ekonomi Pembangunan, 2022)
ABSTRACT Human development is defined as a process to expand more options to the population through empowerment efforts that prioritize improving basic human abilities so that they can fully participate in all areas of development. The Human Development Index (HDI) to measure human development achievements based on a number of basic components of quality of life. Human development is synonymous with poverty reduction and unemployment, and can also be measured through population. The objectives of this study include; to see the direct relationship between total population, poverty, unemployment to the human development index and to see the indirect relationship between total population, poverty and the human development index through unemployment.The results of this study found that: Partially the population (X1) has a negative relationship with unemployment (X3). This is because the value of the correlation coefficient which is negative is -0.013 and the value of the relationship between these two variables is categorized as having no relationship because it is in the range below the value 0. Partially Poverty (X2) has a positive relationship to poverty (X3). This is because the resulting correlation coefficient value is positive at 0.008 and the relationship value of these two variables is categorized as having a very weak relationship because the correlation matrix value is in the range of values ​​below 0.10. Partially the population (X1) has a positive relationship with poverty (X2). This is because the correlation value between the two variables is positive at 0.138 and the relationship value between these two variables is categorized as having a weak relationship because the correlation matrix value is in the range of values ​​above 0.10. Partially Population (X1) does not have a direct relationship to the Human Development Index (Y). This is because the value of the correlation coefficient which is negative is -0.404 and is in the range below 0. Partially Poverty (X2) has no direct relationship to the Human Development Index (Y). This is because the correlation analysis above obtained a negative value of -0.252. Partially Unemployment (X3) has a very weak relationship with the Human Development Index (Y).